Far From 'Easy' Spectroscopy with the 8π and GRIFFIN Spectrometers at TRIUMF-ISAC. (August 2015) - Garrett, P E; Radich, A J; Allmond, J M; Andreoiu, C; Ball, G C; Bender, P C; Bianco, L; Bildstein, V; Bidaman, H; Braid, R; Burbadge, C; Chagnon-Lessard, S; et al.
Abstract: The 8π spectrometer, installed at the TRIUMF-ISAC facility, was the world's most sensitive γ-ray spectrometer dedicated to β-decay studies. A description is given of the 8π spectrometer and its auxiliary detectors including the plastic scintillator array SCEPTAR used for β-particle tagging and the Si(Li) array PACES for conversion electron measurements, its moving tape collector, and its data acquisition system. The recent investigation of the decay of 124 Cs to study the nuclear structure of 124 Xe, and how the β-decay measurements complemented previous Coulomb excitation studies, is highlighted, including the extraction of the deformation parameters for the excited 0 + bands in 124 Xe. As a by-product, the decay scheme of the (7 + ) 124 Cs isomeric state, for which the data from the PACES detectors were vital, was studied. Finally, a description of the new GRIFFIN spectrometer, which uses the same auxiliary detectors as the 8π spectrometer, is given.